Integrasi Kecerdasan Buatan dalam Mewujudkan Pembelajaran Mendalam di Sekolah Dasar - I.R.W Atmojo, Roy Ardiansyah Dwi Yuniasih Saputri, Fadhil PA, Matsuri (Universitas Sebelas Maret, 2025)
The Artificial Intelligence in Education training based on deep learning aimed to improve digital literacy, AI understanding, and the ability of elementary teachers to design adaptive learning. The method included needs analysis, hands-on workshops, and pre-post evaluation. Results showed a significant improvement in teachers’ competence in integrating AI, particularly in designing STEAM-based learning tools. This training positively impacted teaching motivation and classroom learning quality. The program supports the implementation of the Merdeka Curriculum and the fourth SDG (quality education). Further studies are recommended to assess the impact of AI on student learning outcomes and to develop AI-based LMS tailored to elementary education.